KOMIK DIGITAL SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MIN 1 PANDEGLANG - Rosita, Desyi; Aminudin, Aminudin; Hikmah Hayati, Ela (Staisman Press, 2022)
This study aims to produce more interesting learning by using digital comic learning media as a learning innovation in SKI subjects, which are clumps of Islamic Religious Education taught at MIN 1 Pandeglang. This research uses a descriptive qualitative approach with data collection through observation, in-depth interviews and documentation that are related to digital comics learning media. This result from research that by using learning digital comics, this is a complement to SKI learning, meaning that the media is intended to complement the learning materials that students receive in class. The use of this media in learning must use Photoshop, Adobe Design, Corel Draw. So it can be said that digital comic media material with SKI material is suitable for use in learning for elementary/MI children in class. This media provides convenience, attractiveness, and motivation in teaching and learning activities, so that students' desire to learn SKI learning will increase